Partisipasi Komunitas Lokal Dalam Pengelolaan Pariwisata Pantai Dato Di Kabupaten Majene - Wahyu, Wahyu; Azikin, Ruskin; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2020)
The purpose of the study was to determine the forms of community participation in the management of coastal tourism in Dato Majene Regency and community approaches in the management of coastal tourism in Dato, Majene Regency. The number of informants in this research is 8 people. The type of research used is qualitative by selecting certain people who are considered to have knowledge about the participation of local communities in tourism management. The results of the study indicate that the participation of local communities can be said to run according to the rules but not yet optimal. Hal is evidenced by the results of research that has been done in terms of participation in which no property of the general public and local communities Dato Nearby beaches but on the other participation is already running but is not optimal in general. Keywords : Local Community Participation , Dato Beach Tourism Management